Polyphenols of Salix aegyptiaca modulate the activities of drug metabolizing and antioxidant enzymes, and level of lipid peroxidation - Mohd Nauman; R. K. Kale; Rana P. Singh (BMC, 2018)
Abstract Background Salix aegyptiaca is known for its medicinal properties mainly due to the presence of salicylate compounds. However, it also contains other beneficial phytochemicals such as gallic acid, quercetin, rutin and vanillin. The aim of the study was to examine the redox potential, antioxidant and anti-inflammatory activity of these phytochemicals along with acetylsalicylic acid. Methods The redox potential and antioxidant activity of gallic acid, quercetin, rutin, vanillin and acetylsalicylic acid were determined by oxidation-reduction potential electrode method and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, respectively. In ex vivo studies, antioxidant activity of these phytochemicals was determined by lipid peroxidation and carbonyl content assay in the liver of mice. Anti-inflammatory activity was determined by protein denaturation method. Six-week old C57BL/6 mice treated with gallic acid (100 mg/kg body weight) and acetylsalicylic acid (25 and 50 mg/kg body weight) to investigate their in vivo modulatory effects on the specific activities of drug metabolizing phase I and phase II enzymes, antioxidant enzymes and level of lipid peroxidation in liver. Results The order of ability to donate electron and antioxidant activity was found to be: gallic acid > quercetin > rutin > vanillin > acetylsalicylic acid. In ex vivo studies, the similar pattern and magnitude of inhibitory effects of these phytochemicals against peroxidative damage in microsomes and protein carbonyl in cytosolic fraction were observed. In in vivo studies, gallic acid and acetylsalicylic acid alone or in combination, enhanced the specific activities of drug metabolizing phase I and phase II enzymes as well as antioxidant enzymes and also inhibited lipid peroxidation in liver. Conclusions These findings show a close link between the electron donation and antioxidation potential of these phytochemicals, and in turn their biological activity. Gallic acid, quercetin, rutin and vanillin were found to be better electron donors and antioxidants and therefore, might be mainly responsible for the antioxidant properties of S. aegyptiaca, while acetylsalicylic acid provided its maximum anti-inflammatory activity.